Strategi Pembelajaran Anak Usia Dini Pada Masa Pandemi Covid-19 Di Kepahiang - Ayu Azhari; Abdul Rahman; H.M Taufik Amrillah (Insititut Agama Islam Negeri (IAIN) Curup, 2021)
Parents play an important role in helping the growth and development of children. During the pandemic, children are learning from home or distance learning. In this study, what strategies were used by parents during the Covid-19 pandemic at RT 06 Pasar Ujung Kepahiang Village, what were the results obtained and what were the obstacles faced by parents while their children were studying at home. The purpose of this study is to find out what strategies parents use and what obstacles and what are the results of studying at home during the pandemic. This research is descriptive qualitative. the main data sources are parents, children and teachers. Data collection techniques conducted interviews, observations and documentation. From the research it was concluded that as follows: First, the learning strategies of parents during the pandemic are, 1) Time management, 2) Place management, 3) Rewards, 4) Punishment, 5) Technology utilization. Second, parents' obstacles are, 1) Children's concentration is difficult to focus on, 2) Running out of fun ways to learn, 3) Internet access, and 4) Uncertain study time. Third, the results of the children's achievement are, 1) the achievement of religious and moral values, 2) the physical-motor achievement, 3) the cognitive achievement, 4) the socio-emotional achievement, 5) the language achievement, and 6) the artistic achievement